Protection of Civilians and Treatment of Prisoners during War are at Stake: A Comparative Study - Houmine, Mohammed (UIN Sunan Gunung Djati Bandung, 2024)
The atrocities of Israel's aggression perpetrated from 07 October 2023 on the civilian population and the treatment of prisoners of war shocked the world. Western governments have encouraged Israel to continue its tyranny. Many other governments around the world preferred to remain silent despite the presence of International Humanitarian Law (IHL). This has led to a re-launch of the debate on the credibility of IHL and the positioning of International Islamic Humanitarian Law (IIHL) on the world stage. The aim of this study is therefore to compare IHL and IIHL, from a theoretical and practical point of view, in the field of the protection of civilians during war and the treatment of prisoners of war. To do this, we opted for a comparative approach between these two components, both conceptually and functionally. This approach focused, on the one hand, on the main sources of the Sharia, the Quran and the Sunnah, as well as on the opinions of Muslim scholars (ulamas), supported by concrete examples of the application of Islamic norms by the Prophet and the Rashidoun caliphs. On the other hand, it also examined all the conventions, treaties and other documents that constitute the sources of the IHL. From a theoretical point of view, the results showed that there are many similarities between the two laws. In practical terms, however, the IIHL stands out for its concrete form and effective application. These observations led us to recommend that the current world order be rethought in view of the juxtaposition of the IIHL and IHL rules.